1995
DOI: 10.1002/ppul.1950190102
|View full text |Cite
|
Sign up to set email alerts
|

Sputum peroxidase activity correlates with the severity of lung disease in cystic fibrosis

Abstract: Patients with cystic fibrosis (CF) of the same age differ significantly in their degree of pulmonary disease. Based on preliminary observations, we postulated that the activity of myeloperoxidase would be significantly increased in patients with greater structural lung damage than in those with less lung damage. Acid extracts of weighed sputum samples were assayed for lactoferrin concentrations by ELISA. Activities of peroxidase, cathespsin G, and elastase (with and without proteinase 3) were determined by kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 29 publications
(1 reference statement)
3
42
0
Order By: Relevance
“…Neutrophils are considered responsible for the early onset and the promotion of the inflammatory process in CF, which starts within the first year of a CF patient's life (Khan et al, 1995). Several studies investigating the complex relationships between infection and inflammation in CF support the concept that the host inflammatory response is not necessarily proportional to the burden of pathogens in the respiratory tract, although these pathogens may provide the primary stimulus for such responses (Regelmann et al, 1995). Numerous neutrophils are present in the airways (Fig.…”
Section: III Cystic Fibrosis: the Paradox Of Exacerbation Of Neutromentioning
confidence: 99%
“…Neutrophils are considered responsible for the early onset and the promotion of the inflammatory process in CF, which starts within the first year of a CF patient's life (Khan et al, 1995). Several studies investigating the complex relationships between infection and inflammation in CF support the concept that the host inflammatory response is not necessarily proportional to the burden of pathogens in the respiratory tract, although these pathogens may provide the primary stimulus for such responses (Regelmann et al, 1995). Numerous neutrophils are present in the airways (Fig.…”
Section: III Cystic Fibrosis: the Paradox Of Exacerbation Of Neutromentioning
confidence: 99%
“…Strain C is a disease isolate from the airways of a patient with CF. The expression of the genes for cytochrome c biogenesis encoded by PAGI-2(C) could facilitate iron uptake and inactivation of peroxides (10) and thus may confer an advantage for the bac- teria to persist in the CF lung, where they are exposed to iron limitation and oxidative stress (13,32). However, it is not obvious why the presence of a copper homeostasis protein (C21) or a mercuric resistance operon (C84 to C88) could be of advantage for survival in the CF host.…”
Section: Vol 184 2002mentioning
confidence: 99%
“…The host inflammatory response is not necessarily proportional to the burden of pathogens in the airways but the pathogens may trigger these responses. 3 Lung inflammation is hard to quantify, therefore the systemic host inflammatory response is used as a marker of disease activity. It has been shown that inflammatory markers, C-reactive protein (CRP) and neutrophil elastase complex (NEC) fall significantly after a pulmonary exacerbation has been treated with intravenous (IV) antibiotics 4 but circulating markers may not truly reflect the local inflammatory response in the lung.…”
Section: Introductionmentioning
confidence: 99%